Managing statistical misinformation in marketing: A study on consumers’ attitudes and capabilities - Leung, Chi Hong; Chan, Winslet Ting Yan (Asian Journal of Empirical Research, 2023)
This paper discusses various types of misleading statistical information in marketing promotion and explains why it is harmful for customers. The paper also studies the customers’ attitudes to such misinformation and capabilities of managing it. A survey was used to collect data from 210 respondents’ attitudes to analyzing data when purchasing products and 2) studied whether these respondents could properly evaluate such information found in promotional messages. The respondents were students in a university and they were supposed to have sufficient mathematical and logical capabilities of managing statisical information. Respondents showed positive attitudes to data investigation involved in the purchase decision although they lacked the relevant knowledge to process the misleading statisical information. In general, they might not make correct decisions in various deceptive situations. Relevant product information is usually necessary for customers when they have to consider and buy important products. Statistical information can support objective decision making but the misleading one is harmful for customers. More statistical knowledge and other relevant skills are required to enhance the ability of processing misleading information in marketing promotion. The paper suggests a number ways to acquire such knowledge and skills.